Analisis Perbandingan Kinerja Keuangan Perbankan Konvensional Dan Perbankan Syariah Sebelum Dan Selama Terjadinya Pandemi Covid-19 - Syarah Afdhola, Fidya; Lihan, Irham (Fakultas Ekonomi Universitas Gresik, 2023)
The financial sector has an important role in the economy of a country because this sector is the core of the country's economy. Financial statement analysis can be used as a tool to analyze the company's overall management performance. During the Covid-19 pandemic, the financial sector was one of the sectors most affected and experienced a decline in performance. This study was conducted to examine the impact of the COVID-19 pandemic on banking performance using capital adequacy ratios, efficiency ratios and profitability ratios by comparing financial performance between conventional banks and Islamic banks before the COVID-19 pandemic and during the COVID-19 pandemic (Comparative Analysis). The object of this research is banks listed on the Indonesia Stock Exchange in the 2018-2021 period by using quantitative data and the data source used is secondary data in the form of banking quarterly financial reports. Data testing methods used in this study include normality test and hypothesis testing. From the results of the analysis conducted by the Capital Adequacy Ratio (CAR) variable, it shows that there are no significant differences before and during the COVID-19 pandemic, both in conventional banking and Islamic banking. In the Variable Operating Expanse Ratio (BOPO), there are significant differences before and during the COVID-19 pandemic in conventional banking. On the other hand, there is no significant difference before the pandemic and during the COVID-19 pandemic in Islamic banking. While the Return on Assets (ROA) variable, shows that there are significant differences in ROA before and during the COVID-19 pandemic in conventional banking. In addition, there is no significant difference in the Return on Assets (ROA) variable before and during the COVID-19 pandemic in Islamic banking.